Modified control method of a motion compensated gangway - Zhu Jiyue; Weitian Liu; Heng Yang (PLoS ONE, 2026)
With the growing demand for offshore operations such as wind farm maintenance and maritime transportation, motion-compensated gangways are widely employed on vessels to counteract ship motions in roll, pitch, and heave. However, the persistent and unpredictable ship motion disturbance, combined with nonlinearities in hydraulic system makes motion-compensated gangways more complex dynamic characteristics, which brings huge challenges for the controller design. To address the aforementioned problems, this paper proposes an improved cascade control strategy. Specifically, a dynamic model of the motion-compensated gangway, accounting for the ship motion disturbance, is established using Kane’s method, and the coupling between the gangway’s end-effector and ship motions is investigated. A multi-degree-of-freedom velocity compensation strategy is then introduced into the improved cascade control approach. Finally, simulations are included to validate the effectiveness of the proposed control strategy.